The Use of Strategic Cost Management Systems in Measuring the Industrial Production Cycle: A case study, sudanes Sugar Company. - يسري عبد الرحمن السني المقبول (White Nile Journal for Studies and Research, 2020)
The study aimed to know the effect of applying strategic cost management systems in measuring the industrial production cycle, by studying the Sudanese Sugar Company, as well as identifying the extent of the practice and application of strategic cost management systems in the industrial sector in the Sudanese Sugar Company, and to determine the impact of that application in those factories, the study used The descriptive approach relied on the questionnaire as a main tool in collecting primary data from the respondents. A statistical analysis program (spss) was used to analyze the questionnaire and test hypotheses. The study showed a statistically significant relationship between the target cost in supporting the competitive advantage and the continuity of the Sudanese sugar company, as well as a statistically significant relationship between the cost method based on activity in support of the competitive advantage and the continuity of the Sudanese sugar company, and based on these results a number of recommendations were presented, including The need to provide qualified human cadres to apply strategic cost methods, the company’s need to adopt modern cost systems to develop the work mechanism of the Sudanese Sugar Company, that the company works to use raw materials in the best way, that the company uses modern industrial mechanisms that enable A to achieve its objectives, work to recognize the strategic importance of company officials cost methods, the need for the rehabilitation of human resources and training on modern systems, develop a clear strategy to exploit the idle capacity until the company make the most of them, the exploitation of resources optimally to reduce the costs of the company. Keys Worols: Strategic Manag ment Methods, industrial production, Strategic Cost.